Redox mediator assists electron transfer in lithium–sulfur batteries with sulfurized polyacrylonitrile cathodes - Chang‐Xin Zhao; Wei‐Jing Chen; Meng Zhao; Yun‐Wei Song; Jia‐Ning Liu; Bo‐Quan Li; Tongqi Yuan; Cheng‐Meng Chen; Qiang Zhang; Jia‐Qi Huang (EcoMat, 2021)
Abstract The development of next‐generation high‐energy‐density batteries requires advanced electrode materials. Sulfurized polyacrylonitrile (SPAN) is considered a promising sulfur cathode with the merits of high specific capacity and long cycling stability for high‐performance lithium–sulfur (Li–S) batteries. Nevertheless, the practical performances of SPAN cathodes are severely limited by the unfavorable electron accessibility due to the relatively low intrinsic conductivity and large particle size. Herein, a redox mediation strategy is proposed to accelerate the electron transfer processes in working Li–S batteries with SPAN cathodes. Specifically, a quinone‐based redox mediator is introduced to provide an additional redox pathway with strengthened interfacial kinetics. The redox mediator assisted SPAN cathodes exhibit higher specific capacity, improved rate performance, reduced polarization, and longer cycling lifespan with both ether‐based and carbonate‐based electrolyte. This work demonstrates the feasibility of redox mediation to promote the electron accessibility for high‐performance Li–S batteries with SPAN cathodes.